Multidisciplinary Approach of Placenta Accreta Spectrum Management to Reduce Blood Loss and Prevent Organ Injury in Referral Center - Nugraha, Gagah Baskara Adi; Yuliantara, Eric Edwin (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To investigate the differences in blood loss and organ injury at our PAS referral center over the past six years.Methods: This retrospective analytical study included 150 subjects diagnosed with PAS based on histopathological findings from 2018 to 2023 at the PAS Center of Dr. Moewardi Regional Hospital, Surakarta, Indonesia. Subjects were divided into two groups: before 2020 and after 2021, based on multidisciplinary team appointments.Results: The highest number of Placenta Accreta Spectrum (PAS) cases occurred in 2020, with 36 patients. Hysterectomy was the most frequently performed procedure for managing PAS in all groups. However, differences in blood loss, organ injury, and length of hospital stay between the periods from 2018 to 2020 and 2021 to 2023 were statistically significant (p < 0.05).Conclusion: Multidisciplinary approaches involving various medical specialties and teams are essential to ensure maternal safety and effectively manage massive blood loss and organ damage during PAS surgery procedures.Keywords: Placenta accreta spectrum, Blood loss reduction, Organ injury prevention.